Tranexamic acid – a useful drug in ENT surgery?. (14th July 2014) - Robb, P J
Abstract: Background: Tranexamic acid is a synthetic antifibrinolytic drug. It has been widely available for over 40 years, but only recently has it started to be used routinely in many surgical disciplines. For ENT surgeons, epistaxis and post-tonsillectomy bleeding contribute a significant proportion of the morbidity and emergency workload in a general ENT department. Published evidence indicates a potentially helpful role for tranexamic acid in managing epistaxis. Results and conclusion: To date, the benefits of tranexamic acid as a prophylactic treatment to reduce the rate and severity of post-tonsillectomy bleeding are less certain. Two recently published pilot studies looking at primary haemorrhage in children and secondary haemorrhage in adults following tonsillectomy suggest that further large, randomised trials should explore the efficacy of tranexamic acid in routine ENT surgery. There are potential reductions in patient morbidity and cost savings if tranexamic acid is found to be efficacious in larger trials.